Genome-wide identification and comparative analysis of drought related genes in roots of two maize inbred lines with contrasting drought tolerance by RNA sequencing - Lu-yang HAO (Journal of Integrative Agriculture, 2020)
Drought is one of the most important abiotic stresses affecting maize growth and development and therefore resulting in yield loss. Thus it is essential to understand molecular mechanisms of drought stress responses in maize for drought tolerance improvement. The root plays a critical role in plants sensing water deficit. In the present study, two maize inbred lines, H082183, a drought-tolerant line, and Lv28, a drought-sensitive line, were grown in the field and treated with different water conditions (moderate drought, severe drought, and well-watered conditions) during vegetative stage. The transcriptomes of their roots were investigated by RNA sequencing. There were 1 428 and 512 drought-responsive genes (DRGs) in Lv28, 688 and 3 363 DRGs in H082183 under moderate drought and severe drought, respectively. A total of 31 Gene Ontology (GO) terms were significantly over-represented in the two lines, 13 of which were enriched only in the DRGs of H082183. Based on results of Kyoto encyclopedia of genes and genomes (KEGG) enrichment analysis, “plant hormone signal transduction” and “starch and sucrose metabolism” were enriched in both of the two lines, while “phenylpropanoid biosynthesis” was only enriched in H082183. Further analysis revealed the different expression patterns of genes related to abscisic acid (ABA) signal pathway, trehalose biosynthesis, reactive oxygen scavenging, and transcription factors might contribute to drought tolerance in maize. Our results contribute to illustrating drought-responsive molecular mechanisms and providing gene resources for maize drought improvement.